Causes of Landslides in Chittagong Hill Tracks, Bangladesh - Tandrila, Anika Tabassum; Mohiuddin, Md.; Hossain, Mallik Akram; Rahman, Md. Sifatur; Samad, Abdus (National Geographical Journal of India, 2022)
Landslide is a regular hazard in Bangladesh, especially in the Chittagong Hill Tracks (CHT), the Southeastern part of the country. The devastating landslide causes fatalities, injuries and also damage properties of local residents almost every year. Thus the main objective of this research is to determine the triggering factors of landslide. This study is carried out in landslide prone sites located in Rangamati, and Khagrachari area of CHT. Necessary data are collected from both from primary and secondary sources. Primary sources include questionnaire survey, laboratory test and field observation while secondary sources encompass journal article, reports, and meteorological data from Bangladesh Metrological Department. The sample size of the study was 385 respondents. Respondents are selected randomly from the landslide prone area. Soil samples are also gathered from the study site to examine the soil structure that may affect landslide. The present study demonstrates that the main reasons for landslide are heavy rainfall, hill cutting, deforestation, and weak soil structure. Approximately 70 percent of the people in the study area comment that heavy downpour is the dominant factor of landslide followed by hill cutting 17 percent, and deforestation 13.5 percent. The findings of the study will help to understand the driving forces of landslide and provide appropriate guidelines for the policy makers.